2011
DOI: 10.3413/nukmed-0363-10-10
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between GATE4 results and MCNP4B published data for internal radiation dosimetry

Abstract: Despite of differences between the GATE4 and MCNP4B, the results can be considered ensuring. This may be considered as validation of GATE/GEANT as a proprietary code in nuclear medicine for radionuclide dosimetry applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The doses calculated using the voxelized MC simulation are consistent with OLINDA/EXM to within 5%. The agreement between this simulation and OLINDA/EXM is consistent with other comparisons between different Monte Carlo codes for dosimetry [21][22][23].…”
Section: Monte Carlo Dose Calculationssupporting
confidence: 88%
“…The doses calculated using the voxelized MC simulation are consistent with OLINDA/EXM to within 5%. The agreement between this simulation and OLINDA/EXM is consistent with other comparisons between different Monte Carlo codes for dosimetry [21][22][23].…”
Section: Monte Carlo Dose Calculationssupporting
confidence: 88%
“…We inspected the consistency and agreement between the results derived from Penelope, Livermore and Geant4-standard physics models, as well as MIRD S-values, and the corresponding results obtained with Geant4-DNA physics. Pearson's product-moment coefficient was calculated so as to examine the linear relationship, and the Bland-Altman plot to verify the agreements between two series of data (Parach and Rajabi 2011). We calculated the relative difference between the two series of data (RD%) as follows: where S test represents the S-values calculated using the Penelope, Livermore and Geant4standard physics models and also the published MIRD values.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the applicability of the GATE Monte Carlo package for internal dosimetry of radionuclides and related applications [3,4,20,21]. A brief summary of these studies can be found in a published review by Sarrut et al [22].…”
Section: Introductionmentioning
confidence: 98%
“…Each organ in the Zubal phantom has a unique code that identifies its voxels. This phantom has previously been used for internal dosimetry calculations with GATE/Geant4 Monte Carlo package and verified with MCNP4C data [3,4]. Otoko [5], ADELAIDE [6] and Golem [7] are similar examples of computational human models that have been constructed from CT scans of actual patients.…”
Section: Introductionmentioning
confidence: 99%